2011
DOI: 10.1039/c0mt00091d
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the selenium metabolism in cancer cell lines

Abstract: The aim of this work was to compare different selenium species for their ability to induce cell death in different cancer cell lines, while investigating the underlying chemistry by speciation analysis. A prostate cancer cell line (PC-3), a colon cancer cell line (HT-29) and a leukaemia cell line (Jurkat E6-1) were incubated with five selenium compounds representing inorganic as well as organic Se compounds in different oxidation states. Selenomethionine (SeMet), Se-methylselenocysteine (MeSeCys), methylseleni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 28 publications
9
40
1
Order By: Relevance
“…This lack of transformation of the selenoamino acids in Caco-2 cells is in agreement with SeMet and MeSeCys being substrates of amino acid transporters [17]. The same pattern has been observed in studies on biotransformations in the prostate carcinoma (PC-3) and T cell leukemia (Jurkat) cell lines [28]. In addition, size exclusion chromatography revealed that a selenium-containing protein was formed in the cell lysate (Fig.…”
Section: Speciation Analysissupporting
confidence: 65%
“…This lack of transformation of the selenoamino acids in Caco-2 cells is in agreement with SeMet and MeSeCys being substrates of amino acid transporters [17]. The same pattern has been observed in studies on biotransformations in the prostate carcinoma (PC-3) and T cell leukemia (Jurkat) cell lines [28]. In addition, size exclusion chromatography revealed that a selenium-containing protein was formed in the cell lysate (Fig.…”
Section: Speciation Analysissupporting
confidence: 65%
“…Sodium selenite is commonly used as a source of selenium in biological research. Accumulating evidences confirmed the application of selenite in studies of cell proliferation and cancer (3,4). Previous results suggested supranutritional doses of selenite promoted cell death through mitochondria-or ER stress-mediated apoptotic pathway in human leukemia cell lines (5,6).…”
Section: Introductionmentioning
confidence: 70%
“…The (3-CF 3 C 6 H 4 Se) and (4-MeOC 6 H 4-Se) compounds induced cytotoxicity and alterations in cell morphology in HT-29 cells in a dose-dependent manner: 20 μM (24.4 vs. 65.2%), 40 μM (81.8 vs. 81.7%) and 80 μM (91.2 vs. 96.1%), respectively. A recent study evaluated the ability of different selenium compounds (selenate, selenite, MeSeA, MeSeCys and SeMet) to induce cell death in HT-29 cells (Lunøe et al, 2011). The most effective compound was selenite, an inorganic selenium, the percentage of cell death was 21 (10 μM) and 39% (100 μM), followed by two organic selenium compounds, MeSeA (methylseleninic acid) 2 (10 μM) and 14% (100 μM), and MeSeCys (Se-methylselenocysteine) 3% (100 μM).…”
Section: Discussionmentioning
confidence: 99%